″The content of the conception "the culture of professional communication" of the marketers″. - Gogol, I. O. (Problems of Engineer-Pedagogical Education, 2018)
The article analyzes the content of the concept of "culture of professional communication" of marketers in the context of their professional activities. To determine this concept, the meaning of some related terms such as "culture", "communication", "culture of communication", and "communicative culture" are considered. Characteristics of the professional activities of marketing specialists are given; their professional functions which include analytical, production, marketing, managerial and control ones are specified. It is shown that the professional activity of the marketer is subject-subjective and is based on professional interaction whose effectiveness depends on the culture of professional communication of the specialist. On the basis of generalization of the research results it is determined that the culture of professional communication of the marketing specialist is a personal integrative characteristic that ensures the professional subject-subject interaction of the marketer with the consumers of marketing services, which is conditioned by the needs of marketing activity and is aimed at achieving a positive result. The list of subjects of professional communication of the marketing specialist is specified.